IMPROVING MATHEMATIC COMMUNICATION ABILITY CLASS OF VII A STUDENTS SMP NEGERI 11 CIMAHI ON FLAT BUILDING MATERIALS FOUR THROUGH THINK-TALK -WRITE (TTW) APPROACHES - Tupa Minokti; Andriana Siwi Purwandari (IKIP Siliwangi, 2019)
This study aims to increase the mathematical communication skills of students at class VII A on rectangular flat material through the Think-Talk-Write (TTW) approach in SMP Negeri 11 Cimahi. This type of research is CAR or Classroom Action Research using a model from Kemmis and McTaggart with spiral research, the population sample are all students of class VII A Cimahi 11 Public Middle School consisting of 36 students. This study to be composed of 3 cycles in which each cycle to be composed of the 3 stages that is planning, implementation, and observation reflection, before and after the study was given an instrument test in the form of a description test. In each cycle there is an activity observation sheet. The results of this study indicate that students' mathematical communication skills can be increase through the Think-Talk-Write (TTW) approach application.